Notating heritage musics: preservation and practice in Thailand, Indonesia and Malaysia - Hood, Made Mantle (Universiti Pendidikan Sultan Idris, 2016)
Historically, notation in Southeast Asia has been used for musical documentation and preservation rather than functioning as a medium for realising music during performance. As a consequence, today both heritage and hybrid forms of script such as Balinese ding dong notation and Javanese kepatihan cipher notation play only a minor role in the musical expression of this region’s predominantly aural-based forms. When musical notation is used, it may be found written on a variety of traditional and modern medium including palm leaves and plain paper to computer programs with specialised fonts or even cell phone text messages. In this article, I observe notation in three distinct traditions existing along a continuum from preservation to innovation. Despite technological advancements and the availability of Western staff notation, diverse forms of indigenous musical notation primarily serve to sustain traditions and aide the memory of musicians for teaching and learning.